Analisis Sosiologi terhadap Tradisi Malam Tujuh Likur di Desa Ilath Kabupaten Buru - Hermansyah Hermansyah; Sudirman Sudirman; Arlita Dahlan Fattah (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
Tradition is a series of values, to support life and culture. The residents of Ilath Village, Buruh Regency, have various traditions, including the seven likur night tradition. This tradition is carried out on the last 10th night of the month of Ramadan. This activity starts from the preparation stage to the implementation. The series of activities carried out starting from cleaning the house, road, grave, preparing ketupat jiwa, damar, collecting pieces of banana stems, praying together, and distributing ketupat jiwa which are distributed to widowers or widows, and orphans, and the residents of Ilath in general illustrates collective awareness. The implementation of the seven likur night tradition is marked by the burning of damar which is carried out after the Maghrib prayer. The light of the damar as a symbol of connectedness between residents, is also a symbol of welcoming a night full of blessings from other months. In addition to burning damar, residents also prepare and deliver ketupat jiwa to the Mosque after the Isya prayer, which will later be read a prayer together led by the Khotib after the Tarawih prayer. After the ketupat jiwa has been prayed for, the children and the gods also take part in distributing the ketupat jiwa to the widowers or widows, and orphans in the area.